2024
DOI: 10.5194/acp-24-185-2024
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of vertical mixing, boundary layer schemes, and temporal emission profiles on tropospheric NO2 in WRF-Chem – comparisons to in situ, satellite, and MAX-DOAS observations

Leon Kuhn,
Steffen Beirle,
Vinod Kumar
et al.

Abstract: Abstract. We present WRF-Chem simulations over central Europe with a spatial resolution of 3 km × 3 km and focus on nitrogen dioxide (NO2). A regional emission inventory issued by the German Environmental Agency, with a spatial resolution of 1 km × 1 km, is used as input. We demonstrate by comparison of five different model setups that significant improvements in model accuracy can be achieved by choosing the appropriate boundary layer scheme, increasing vertical mixing strength, and/or tuning the temporal mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A study by Douros et al (2023) reveals overestimations of the winter-time NO 2 VCD by +50 %, and demonstrates that such biases even occur in ensemble models, such as CAMS (consisting of 11 different RCT models with 0.1°× 0.1°horizontal resolution). In previous work, we showed that a recalibration of the vertical mixing parametrization can mostly resolve such biases in the WRF-Chem model in summer over Europe (see Kuhn et al (2024)). However, the process of model recalibration is tedious, computationally expensive, and domain-dependent.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…A study by Douros et al (2023) reveals overestimations of the winter-time NO 2 VCD by +50 %, and demonstrates that such biases even occur in ensemble models, such as CAMS (consisting of 11 different RCT models with 0.1°× 0.1°horizontal resolution). In previous work, we showed that a recalibration of the vertical mixing parametrization can mostly resolve such biases in the WRF-Chem model in summer over Europe (see Kuhn et al (2024)). However, the process of model recalibration is tedious, computationally expensive, and domain-dependent.…”
Section: Introductionmentioning
confidence: 94%
“…The simulation was run for the month of May 2019 on a domain over Europe with a spatial resolution of 3 km × 3 km, 43 terrain-following pressure levels, and hourly output. A detailed description, discussion, and validation study of this dataset was published in Kuhn et al (2024). The simulation setup additionally deploys the vertical emission profiles from Bieser et al (2011).…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations